A Near‐Zero Index Metamaterial Lens for Reduced Complexity and High‐Performance Active Electronically Scanned Arrays - J. Daniel Binion; Colin A. Mussman; Erik Lier; Thomas H. Hand; Douglas H. Werner (Advanced Electronic Materials)
Abstract A lens consisting of an anisotropic near‐zero index metamaterial (NZIM) is introduced for improving the far‐field performance of active electronically scanned arrays (AESA). Several simulation studies demonstrate how the NZIM lens (metalens) can be functionalized to transform the embedded element pattern of an array from a typical cosinusoidal shape to a flat‐topped pattern, dramatically reducing the gain at wider angles. This corresponds to reductions in scan loss and suppression of grating lobes in the desired field of view (FOV), especially for arrays with large element spacing (i.e., sparse or thinned arrays). The metalens concept is demonstrated through several simulation studies illustrating the beam shaping capability of NZIM materials. A fabricated metalens demonstrates full suppression of grating lobes and minimal scan loss with a ±10° FOV, which is ideally suited for limited FOV applications such as geosynchronous satellite communications.